Motivasi Berprestasi Memediasi Pengaruh Kompetensi Dan Insentif Terhadap Kinerja Karyawan Pada PT. Golden Roof Polymer Area Daerah Istimewa Yogyakarta - Anindya Silvyana Dwiningtyas; Endah Winarti H.S; Mochanmad Taufiq (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to analyze the influence of competence and incentives on employee performance which is mediated by achievement motivation. The population in this research is all employees of PT. Golden Roof Polymer Area Yogyakarta, totaling 234 people. The samples taken were 146 using the purposive sampling method. The data analysis method uses regression and data processing uses SPSS 23 software. The results of hypothesis testing show that competence has a positive and significant effect on organizational commitment. Incentives have a positive and significant effect on achievement motivation. Achievement motivation has a positive and significant effect on employee performance. Competence has a positive and significant effect on employee performance. Incentives have a positive and significant effect on employee performance.The results of the Sobel test also show that the indirect influence of competence on employee performance is significant, this shows that the achievement motivation variable can mediate the influence of competence on employee performance. The indirect effect of incentives on employee performance is significant, this shows that the achievement motivation variable can mediate the effect of incentives on employee performance.